Assessment of food-drug interaction knowledge among Turkish healthcare professionals - Ugur Balaban; Tuba Yildiz Balaban; Burcu Kelleci Cakir (BMC Medical Education)
Abstract Background Food-drug interactions (FDIs) can affect drug efficacy and patient safety, potentially leading to therapeutic failures or adverse events. Despite their clinical relevance, FDIs are often overlooked in practice. This study aimed to assess FDI knowledge among Turkish healthcare professionals (HCPs) and identify factors associated with knowledge proficiency. Methods A web-based, cross-sectional survey was conducted between February and March 2025 among HCPs, including pharmacists, physicians, nurses, and other allied HCPs. FDI knowledge was assessed using a validated 21-item scale, with scores categorized as low (0–5), moderate (6–10), good (11–15), and very good (16–21). Multivariable quantile regression analysis was performed to determine factors associated with higher FDI knowledge scores. Results A total of 418 HCPs participated, with a median FDI knowledge score of 13 (interquartile range [IQR]: 7) out of 21. Pharmacists had the highest median score of 15 (5), followed by physicians with 12 (6), nurses with 10 (7), and other allied HCPs with 10 (6) (p < 0.001). Level of knowledge varied significantly across professions, with 25.4% of participants categorized as “very good,” 36.4% as “good,” 29.2% as “moderate,” and 9.1% as “low.” Multivariable regression identified profession and higher education level as significant predictors of FDI knowledge. Pharmacists had significantly higher scores across all percentiles (p < 0.001). HCPs with a doctorate or equivalent specialty demonstrated significantly higher scores at the 25th (p = 0.011), 50th (p < 0.001), and 75th (p = 0.008) percentiles. Similarly, those with a master’s degree had significantly higher scores at the median percentile (p < 0.001). Sex, age, and years of professional experience were not significant determinants (p > 0.05). Conclusions This study reveals substantial variability in FDI knowledge among HCPs, with pharmacists demonstrating the highest proficiency. However, critical knowledge gaps remain across all professional groups. Addressing these gaps is critical for optimizing pharmacotherapy and ensuring patient safety. Given the risks of unrecognized FDIs, structured educational interventions are urgently needed to improve clinical decision-making and reduce preventable potential FDIs related to adverse events.